Curating the Social Fabric: Practice Modes of Art and Cultural Work and their Impact on Social Sustainability in Rural Regions - Huszka Victoria; Müller Oliver; Sutter Ove (European Countryside, 2025)
We examine in our article how art and cultural activities in rural regions can support social sustainability by fostering local social relations, social cohesion and cultural participation. Our analysis draws on four ethnographic case studies in four different rural areas in Germany. We argue that the impact of art and cultural practices on the social fabric of villages and small towns should not only be examined regarding art and cultural activities in a narrow sense i.e., the activities defined as “artistic” and “cultural”. Instead, it is necessary to consider more comprehensively the actors’ social, economic and political activities as well as the local and material environments connected to them. Drawing on cultural and social practice theory, we analyze four modes of practice of art and cultural work distinguished by different ways of working on the social fabric in rural regions: artist mode, social worker mode, cultural entrepreneur mode and activist mode. The differences observed between these modes of practice and their impacts on social sustainability amount, in part, to different understandings of art and culture held by cultural workers themselves but also unfold regarding the socioeconomic and spatial contexts of the cultural initiatives investigated.